Optimization of dairy based farming agricultural in critical land area of Yogyakarta Special Territory - Elan Masbula (Indonesian Center for Animal Research and Development (ICARD), 1999)
A study has been done to provide a conceptual basis for the development of agricultural system in critical land area in Yogyakarta Special Teritory as the smallest production unit to (1) determine optimum dairy farming based agriculture for the area and income maximization on either farmer own inputs or with CAFlTAL aid provided by a funding party, (2) to develop a model for developing farming system based on dairy farming in critical land area in Yogyakarta Special Teritory.Methods being used multistage problem solving approach to the problem encountered in farming system as practiced in Glagaharjo Village, Sub District of Cangkringan, Sleman with Rapid Rural Appraisal (RRA) and Agro-ecosystem Analysis as diagnostic activities. Farm record keeping and survey to fourty respondents purposively selected were then conducted. Using Linear Programming (LPM), a normative solution, under the imposed constraints for each activity, was obtained to see development effectivity of dairy based farming agricultural system. The result indicated that land resources had not managed optimally. Out of an average possession of 1,5 ha dry land, only 0,6 ha was cultivated, leading to relativelly low yield and income. Optimum dairy farming agriculture migh be an option to develop the area. Dairy farm Cooperative Agency (Model of Scenario I) can play important role to improve farmer income. With an average of 1,5 ha dry land and an average of 3 Animal Unit raised would optimized the resources allocation and income of Rp.20,385,340 for a period of eight years. The income rnigh be further increased to Rp.36,176,070 for similar production period with soft loan provided by ventura fund (Model of Scenario ll) to optimize land resources and family labor force use and a farmer was able to raised an average of 4 Animal Unit. If as being planned - such as scheme is adopted by 1,400 farmer, 230 worker will be employed in the first years. Employement need is increasing with time and after eight year it may reach 1154 workers/year. It can then be concluded that dairy based farming agriculture may improved economic endurance of farmer in critical land area, and directed as well toward land conservation program. Key words: Optimization, farming system, dairy based farming